KONTRIBUSI PERAMALAN PENERIMAAN MAHASISWA BARU POLITEKNIK : SEBAGAI ALAT ESTIMASI PENDAPATAN - Ahmad Mustofa; Nurafni Eltivia; Zainal Abdul Haris (Media Mahardhika, 2020)
Purpose of this research was to determine the forecasting results of new student admissions and the estimated amount of income from a recurrent academic fees. The data was secondary data from the list of enthusiasts and the capacity of new students. This research was quantitative descriptive and using Mean Absolute Percentage Error (MAPE), Mean Squared Error (MSE), Mean Absolute Deviation (MAD) as a calculation of the level of error accuracy, and single exponential smoothing method as forecasting of new student admissions. Forecasting results obtained DIII Accounting enthusiasts and capacity totaling 2951 and 181 students for 2020 while 2186 students and 191 students for 2021. For the DIV Management accounting produces 4184 and 238 students interested, 238 students for 2020, whereas in 2021 produced 5106 enthusiasts and 226 students for capacity of new students. the total estimated revenues in 2020 and 2021 have a significant amount of interest from new students and the interest of new students through a recurrent academic fees. It was concluded that forecasting can also be used to calculate the estimated income in an institution or even a company so that this paper will contribute to the field of information and finance that can help in decision making.